Band structure of non-steiochiometric large-sized nanocrystallites - Kityk, I.V. (Condensed Matter Physics, 2004)
A band structure of large-sized (from 20 to 35nm) non-steichiometric nanocrystallites (NC) of the Si₂₋xCx (1.04 <x< 1.10) has been investigated using different band energy approaches and a modified Car-Parinello molecular dynamics structure optimization of the NC interfaces. The nonsteichiometric excess of carbon favors the appearance of a thin prevailingly carbon-contained layer (with thickness of about 1 nm) covering the crystallites. As a consequence, one can observe a substantial structure reconstruction of boundary SiC crystalline layers. The numerical modeling has shown that these NC can be considered as SiC reconstructed crystalline films with thickness of about 2 nm covering the SiC crystallites. The observed data are considered within the different one-electron band structure methods. It was shown that the nano-sized carbon sheet plays a key role in a modified band structure. Independent manifestation of the important role played by the reconstructed confined layers is due to the experimentally discovered excitonic-like resonances. Low-temperature absorption measurements confirm the existence of sharp-like absorption resonances originating from the reconstructed layers.